Pancake-Like MOF Solid-State Electrolytes with Fast Ion Migration for High-Performance Sodium Battery - Zhang, Gang; Shu, Jun; Xu, Lin; Cai, Xinyin; Zou, Wenyuan; Du, Lulu; Hu, Song; Mai, Liqiang (Nano-Micro Letters, 2021)
Solid-state electrolyte (SSE) of the sodium-ion battery have attracted tremendous attention in the next generation energy storage materials on account of their wide electrochemical window and thermal stability. However, the high interfacial impedance, low ion transference number and complex preparation process restrict the application of SSE. Herein, inspired by the excellent sieving function and high specific surface area of red blood cells, we obtained a solid-like electrolyte (SLE) based on the combination of the pancake-like metal–organic framework (MOF) with liquid electrolyte, possessing a high ionic conductivity of 6.60 × 10–4 S cm−1, and excellent sodium metal compatibility. In addition, we investigated the ion restriction effect of MOF’s apertures size and special functional groups, and the ion transference number increased from 0.16 to 0.33. Finally, the assembled Na0.44MnO2//SLE//Na full batteries showed no obvious capacity decrease after 160 cycles. This material design of SLE in our work is an important key to obtain fast ion migration SLE for high-performance sodium-ion batteries. Highlights: 1 A pancake-like morphology solid-like eletrolyte of sodium battery with high ionic conductivity (6.60 × 10–4 S cm−1) was obtained by simple hydrothermal method. 2 Solid-like electrolyte with pancake-like morphology showed good interface contact and excellent compatibility (stable cycle over 500 h at 0.6 mA cm−2) with sodium metal. 3 Provides possible repulsive force explanation for the restriction of ion transport by MOF.